2003
DOI: 10.1089/107632703764664774
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Submucosa Induces Loss of Mitochondrial Integrity and Caspase-Dependent Apoptosis in Human T Cells

Abstract: Porcine small intestinal submucosa (SIS) is a cell-free biomaterial used in humans for wound healing and as scaffold material for constructive remodeling of damaged or missing tissue. We have previously shown that SIS contains a factor that suppresses human helper T cell subset differentiation and expansion by inducing programmed cell death. Our aims here were to identify in detail the processes involved in SIS-induced T cell apoptosis and to perform the first characterization of the apoptosis-inducing factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…73 In contrast to results reported by Allman et al, SIS completely abolishes the generation of Th2 cells in vitro; and the suppression of Th cell activation by SIS involved the induction of Th cell apoptosis through a caspase-dependent pathway(s), but independent of TGF-b, Fas ligand (FasL), or galectin family members. 74 Other studies showed that SIS appears to have no effects on proinflammatory cytokines (IL-6, IL-1b, TNF-a) or NLRP3 expression, but promotes both Th1 and Th2 responses under different conditions. 70 Sterilization methods such as freeze-drying and gas sterilization may have significant impacts by activating or inactivating unidentified bioactive molecules in SIS and eliciting differential biological responses.…”
Section: Inflammatory Responses In Sis-augmented Bladdersmentioning
confidence: 99%
“…73 In contrast to results reported by Allman et al, SIS completely abolishes the generation of Th2 cells in vitro; and the suppression of Th cell activation by SIS involved the induction of Th cell apoptosis through a caspase-dependent pathway(s), but independent of TGF-b, Fas ligand (FasL), or galectin family members. 74 Other studies showed that SIS appears to have no effects on proinflammatory cytokines (IL-6, IL-1b, TNF-a) or NLRP3 expression, but promotes both Th1 and Th2 responses under different conditions. 70 Sterilization methods such as freeze-drying and gas sterilization may have significant impacts by activating or inactivating unidentified bioactive molecules in SIS and eliciting differential biological responses.…”
Section: Inflammatory Responses In Sis-augmented Bladdersmentioning
confidence: 99%
“…Its efficacy in promoting tissue growth, differentiation and angiogenesis has been well documented [5]. In addition, it has also been reported to possess some immunosuppressive factors [5,7,8]. Based on this, we have speculated that angiogenic potential and immunosuppressive properties of SIS would promote the graft survival of autotransplanted parathyroid tissue.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the integrity of endometrium in the SIS group was better than that in the control group. It has been reported that SIS contains factors with immunosuppressive properties and suppresses the T-helper cell activation [15,16]. Furthermore, it was observed that the implantation of SIS is associated with fewer infections than other graft materials [14].…”
Section: Discussionmentioning
confidence: 99%